The structure of intensity of play in ice hockey - Gabrys, T.; Szmatlan-Gabrys, U.; Stanula, A.; Garnys, M. (World Congress of Performance Analysis of Sport IX, 2012)
Ice hockey game is characterized by high speed and dynamics connected with short-term intensive efforts of players. Ice hockey is a high-speed and dynamic game characterized by short, intense bursts of energy. A hockey player stays on the ice during 25-30s. A hockey player is actively involved in the game for 25-30s. During one "change" the competitor plays with maximum intensity during 3-4s, alternating with the work of low intensity during 5-6s. Competitors of attack formations: the middle and the front, are burdened with an effort of similar intensity. By contrast, the work of defenders is about 1/3 less than maximum intensity. The effort of hockey player throughout the whole game is characterized by submaximal and maximal intensity, which is interrupted by the period of waiting for change. The aim of the research was the assessment of the intensity of effort of 18-year-old Polish hockey team participating in the World Championships in ice hockey. The study involved a group of 15 hockey players 17-18 years old of Polish national team during the World Championship U-18. During ramp test performed on an ergometric bicycle Monark 814 E the degree of load corresponded to 1 Wxkg-1 of body weight. In the ramp test using an ergonometric bicycle Monark 814 E the load was set at 1 Wxkg-1 of body weight. Each following level was higher by 0.5 Wxkg-1 of body weight. During the effort on the analyzer K4b2 (Cosmed, Italy) the volume of oxygen consumption (VO2) was recorded, and using a heart rate monitor Polar Team (Polar OY, Finland), the contractions of the heart were registered. Basing on the work of, where Energetic classification of effort intensity during a game were estimated [Flanagen & Merrick 2002]. Classification is based on the values of oxygen consumption and the corresponding heart contractions. Five areas of effort intensity was obtained: VHI - area of very high effort intensity - 86-100% VO2max, HI (76-85%), MI (51-75%), LI (31-50%), AR (15-30%), SR (= 14%). For each tested player the above mentioned areas were set on the base of VO2 values, recorded during the progressive effort. The next step was to assign the corresponding values of heart contractions (HR) to the individual VO2. Thus the individual ranges of heart contraction values were obtained for each player in each area of intensity. During three games of the World Championship the frequency of heart contractions during a game was recorded by heart rate monitor Polar Team. During three games at the World Championship the frequency of heart contractions was recorded with a Polar Team heart rate monitor. Based on the intensity of the individually determined areas of intensity, the time of staying in each determined sphere of intensity was assigned to each tested player. This time is expressed as a percentage of the total time of period. Position of hockey player in the game determines the structure of the effort intensity during a match. The players of the attack, besides performing the majority of their work in MI area (25,40-38,11%) and VHI area (20,79-37,21%), works in large extent in HI area (17,70-25,08%). The work of LI intensity is performed by attack formation players very rarely (11,93-23,31%). But for the competitors playing in defense, MI (25,62-36,50%) dominated, rarely - LI (17,76-29,92%) and HI (18,46-29,22%). Very rare the effort of the defenders has VHI character (9,02-18,88%).